Investment attractiveness of special economic zones in Lower Silesia in Poland for Japanese FDI - Osmolak, Jarosław (Atrakcyjność inwestycyjna specjalnych stref ekonomicznych na Dolnym Śląsku w Polsce dla japońskich BIZ, 2019)
The aim of the article is to demonstrate the key facts on the matter of investment attractiveness of Polish Special Economic Zones (SEZs) for Japanese Foreign Direct Investment (FDI). The author questioned the notion of public aid intensity in the Dolnośląskie Voivodeship as a key component of investment attractiveness for Japanese FDI. The research methods covered: examining documents, diagnostic survey, desk research as well as study cases. Own research proved that Japanese FDI in the area of Polish SEZs are located mostly in the Wałbrzyska SEZ. Further results are that the Lower Silesian SEZs attracted the most companies from Japan in comparison with other SEZs in Poland. Thus, the crucial factors that determined the choice of SEZs in the Dolnośląskie Voivodeship by the Japanese are as follows: convenient location, positive investment climate, labour costs, industrial traditions and available tax incentives
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 90-102
Keywords: economic zones; investment attractiveness; Japanese FDI; public aid in the European Union; strefy ekonomiczne; atrakcyjność inwestycyjna; japońskie BIZ; BIZ; pomoc publiczna w Unii Europejskiej